2020
DOI: 10.1007/s11126-020-09859-7
|View full text |Cite
|
Sign up to set email alerts
|

Embracing Technology for Capacity Building in Mental Health: New Path, Newer Challenges

Abstract: Technology driven capacity building initiatives are the way to break the barrier of shortage of mental health human resources in India. This new path, while is a welcome step, comes with its own set of challenges. In one prototypic project that is being implemented in Ramanagara District of Karnataka, a south Indian state, we encountered many such issues. They ranged from issues related to availability of dedicated space to set up the hub-studio, inconsistent internet connectivity (particularly in remote areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These were chosen based on the extensive experience of the researchers and with the consensus of experts about the appropriateness and scoring pattern of the questionnaire. This is an eye-opener in (Malathesh et al, 2020).…”
Section: Methodological Issuesmentioning
confidence: 96%
“…These were chosen based on the extensive experience of the researchers and with the consensus of experts about the appropriateness and scoring pattern of the questionnaire. This is an eye-opener in (Malathesh et al, 2020).…”
Section: Methodological Issuesmentioning
confidence: 96%
“…Further, a randomized controlled trial is underway to prospectively compare the outcomes of the traditional training module and digitally driven training module on a number of patient related outcomes (22). In addition to opening newer avenues to overcome the traditional barriers, use of technology are associated with a few challenges as well, particularly when we talk about the field level workers (23). Clearly, more data is needed in this area.…”
Section: Implementation Research Evaluating Outcomes Of Digital Train...mentioning
confidence: 99%
“…[ 8 ] These results hold a lot of promise in scaling up their involvement in integrating mental health care into primary health care (Ibrahim et al , 2021; Malathesh et al , 2021). [ 7 9 ] It is imperative, however, to understand the perspectives of ASHAs and other stakeholders with regard to the delivery of mental health services at the grass-root level. The objective of this study is to explore the qualitative aspects of these newly identified community mental health workers (ASHAs) in terms of service provision and foster a template for further expansion of the same whilst developing an adequate feedback system to enhance which discussions with experts in the field of community mental health have been included.…”
Section: Introductionmentioning
confidence: 99%